Association of Biomarker Levels with Severity of Asbestos-Related Diseases - Eun-Kee Park; Deborah H. Yates; Jenette Creaney; Paul S. Thomas; Bruce W. Robinson; Anthony R. Johnson (Elsevier, 2012)
Objectives: Asbestos-related diseases (ARDs) have increased globally over the decades, causing an economic burden and increased health care costs. It is difficult to predict the risk of development of ARDs and of respiratory disability among workers with a history of asbestos exposure. Blood based biomarkers have been reported as promising tools for the early detection of malignant mesothelioma. This study investigated whether serum soluble mesothelin-related peptide (SMRP) would reflect severity of disablement in compensable ARDs. Methods: SMRP levels were measured in a cohort of 514 asbestos-exposed subjects. Severity of ARDs was assessed by a Medical Authority comprising four specially qualified respiratory physicians. Severity of ARDs and SMRP levels were compared. Results: Mean (standard deviation) serum SMRP level in the population with compensable ARDs (n = 150) was 0.95 (0.65) nmol/L, and was positively associated with disability assessment (p = 0.01). Mean SMRP level in healthy asbestos-exposed subjects was significantly lower than those with pleural plaques (p < 0.0001) and in subjects with ARDs who received compensation (p < 0.01). Conclusion: This study indicates that serum SMRP levels correlate with severity of compensable ARDs. Serum SMRP could potentially be applied to monitor progress of ARDs. Further prospective work is needed to confirm the relationship between SMRP and disability assessment in this population.